Anti-inflammatory effect of two pomegranate seed oils obtained by green technologies in Caco-2 cells using the bioaccessible fraction from in vitro gastrointestinal digestion. (March 2023) - Bañares, Celia; Carballeda-Sangiao, Noelia; Chabni, Assamae; García-Cordero, Joaquin; Reglero, Guillermo; de Pascual-Teresa, Sonia; Torres, Carlos F.
Graphical abstract: Highlights: Expeller and supercritical CO2 extracted pomegranate seed oil has good bioaccessibility. The expeller extracted pomegranate seed oil has the largest amount of micellar phase. A large fraction of mixed micelles are formed during the in vitro digestion process. Cell monolayer integrity is protected against LPS in the presence of expeller extracted pomegranate seed oil. Reduction of IL-6, IL-8 and TNF-α is found in presence of expeller extracted pomegranate seed oil. Abstract: Pomegranate seeds contain up to 20% oil with a high content of punicic acid (85%), which is responsible for several biological activities. In this work, two pomegranate oils obtained by a two-step sequential extraction, first with an expeller and then via supercritical CO2 technologies, have been studied in a static gastrointestinal in vitro digestion model to evaluate their bioaccessibility. The micellar phases obtained were evaluated by an in vitro model of intestinal inflammation and Caco-2 cells exposed to the inflammatory mediator lipopolysaccharide (LPS). Inflammatory response was assessed by measuring the production of interleukins IL-6 and IL-8, and tumor necrosis factor α (TNF-α), and by evaluating the monolayer integrity. The results obtained indicate that expeller pomegranate oil (EPO) provides the highest amount of micellar phase ( ca . 93%) with free fatty acids and monoacylglycerols as major components. The micellar phase obtained with supercritical CO2 pomegranate oil (SCPO) is ca . 82% with similar lipid composition. Micellar phases of EPO and SCPO showed high stability and adequate particle size. EPO shows an anti-inflammatory response, reducing the production of IL-6, IL-8 and TNF-α in LPS stimulated caco-2 cells and increasing the integrity of the cell monolayer as measured by transepithelial electrical resistance (TEER). In the case of SCPO, the anti-inflammatory effect was only evident for IL-8. The present work demonstrates good digestibility, bioaccessibility and anti-inflammatory response of both EPO and SCPO oils.